Analisis nilai CT Number pada pemerikasaan CT Scan Thorax pada Kasus Efusi Pleura di RS Bhayangkara Makassar - Puspaningrum, Sania; Jeniyanthi, Ni Putu Rita; Darmita, I Made Purwa (Nautical : Jurnal Ilmiah Multidisiplin Indonesia, 2023)
The goal of this study was to find out what the CT number meant on a thorax CT scan in Pelura Effusion cases at Bhayangkara Hospital Makassar. This study used a quantitative descriptive study with an observational approach. Based on the results of the research conducted, researchers can conclude that there is an influence of the CT number value on the thorax CT scan examination in pleural effusion cases. In the research that was conducted, the researchers obtained a sample of 2 patients with pleural effusion cases at the Radiology Installation at Bhayangkara Hospital, Makassar. A chest CT scan of a case of non-contrast pleural effusion revealed dense free fluid in the pleural vacuum in the first patient. With the coronal section, the maximum HU value is 22.56 HU and the minimum value is 2.47 HU, while the maximum HU value on the axial section is -7.06 HU and a minimum value of -31.31 HU. In the second patient, the maximum value of the coronal section was 22.09 HU and the minimum value was 9.88 HU, while the axial section had a maximum value of 24.09 HU and a minimum value of 12.25 HU.